Uso de jogos digitais no processo de alfabetização: possibilidades de avanço nos níveis da escrita - Andrade, Maria Aparecida Alves de (2020)
Given the fact that digital games are still little explored in the classroom as a resource for teaching and learning in the literacy phase, this study proposes to verify the possibilities and limitations of free and pre-selected digital games for writing learning in a group of students of the last stage of kindergarten in a private school at Natal. To this end, a collection of digital games, selected using an analysis instrument elaborated by Vilarinho e Leite (2015), converging with the theoretical principles of Piaget (1974) and Vygotsky (2005) and conceptualization of writing levels established by scholars Emilia Ferreiro and Ana Teberosky (1989), as well as literacy concept by the linguist Magda Soares (2002) was organized. Our problematic comes from the following question: What are the possibilities and limitations of free digital literacy games selected for the development of the children’s writing levels in the process of literacy? To answer such questions, the theoretical foundation is based on concepts of literacy and initial reading instruction, digital gaming and child. The method used for the investigation was characterized as an exploratory approach supported by documentary and bibliographic research, analytical and qualitative nature. Based on the data collected from the games’ application, the research culminated in presenting an analysis of the possibilities and limitations of digital games used for the literacy process, especially the acquisition of written language.